New results from a beta-Pareto class - Makgai, S. L.; Bekker, A.; Ferreira, J. T.; Arashi, M. (South African Statistical Journal, 2017)
In this paper, we propose new results on a beta-Pareto class. This extension evolved by using newly proposed class of beta distributions as generator distributions (F(x)) within the generator-parent approach: H(x) = F(G(x)) with G(x) the Pareto distribution as the parent distribution. Fundamental properties are studied, including moments and Rényi entropy. We illustrate the added value to the literature with a numerical example using hydrology data, indicating that this newly proposed class is a valid candidate to consider in modelling within the hydrology arena.